(untitled) (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
In the increasingly competitive media landscape newspapers, among others, are under pressure from digital and social media. As a result, the performance and positioning of traditional Afrikaans newspapers like Rapport, Beeld, Die Burger and Volksblad, as well as the forms of Afrikaans they use, are constantly scrutinised in surveys about the relevance and profitability of the Afrikaans print media. These surveys often point to the use of Afrikaans ‘as spoken by the people’ in emerging newspapers like Son and, Son op Sondag, as the main reason for the growing popularity, healthy sales figures and advertising revenue of these two newspapers. As a result, Son developed into the largest Afrikaans daily in an Afrikaans print market long dominated by established titles like Beeld, Die Burger and Volksblad. In view of this, this contribution will firstly investigate the profitability (in monetary terms and circulation) of actually using Kaaps in newspapers. Secondly, it will focus attention on the use of this form of Afrikaans in traditional newspapers in which Standard Afrikaans is the dominant form. The question is: What is the nature of the Kaaps in these newspapers compared to the Kaaps in Son specifically? The aim of this contribution is to explore how Afrikaans newspapers create space for the use of colloquial varieties in general and Kaaps specifically, and to determine the relevance or function of Kaaps in the news domain. On the one hand the focus will be on columns in which Kaaps is the medium and on the other, on newspaper articles about the Afrikaans language variety. The data on which this paper is based were firstly, the responses to a list of questions posed to the news-editor of Son, and secondly a critical content analysis and interpretation of the manifestations of Kaaps in this newspaper in comparison to the forms in the more established Afrikaans newspapers. The general perceptions of, and attitudes towards, the use of colloquial varieties of Afrikaans, collated in a 2012 survey among readers, are also taken into account.